Epistemic divides and ontological confusions: The psychology of vaccine scepticism - Matthew Browne (Taylor & Francis Group, 2018)
Vaccine scepticism is an increasingly important barrier to optimal coverage in developed countries. In this commentary, we make the case that negative attitudes towards vaccines reflect a broader and deeper set of beliefs about health and wellbeing. We suggest that this alternative worldview is influenced by ontological confusions (e.g. regarding purity, natural energy), and knowledge based on personal lived experience and trusted peers, rather than the positivist epistemological framework. Our view is supported by recent social-psychological research, including strong correlations of vaccine scepticism with adherence to complementary and alternative medicine, magical health beliefs, and conspiracy ideation. For certain well-educated and well-resourced individuals, opposition to vaccines represents an expression of personal intuition and agency, in achieving a positive and life-affirming approach to health and wellbeing. These core beliefs are not amenable to change - and especially resistant to communications from orthodox, authoritative sources. Although this view does suggest tactical improvements to messaging, we suggest that a better long-term strategy is to combine with other disciplines in order to address the root causes of vaccine scepticism. Vaccine scepticism is unlikely to thrive in a cultural context that trusts and values the scientific consensus.